Common and unique features of glycosylation and glycosyltransferases in African trypanosomes. Issue 17 (16th September 2022) - Duncan, Samuel M.; Ferguson, Michael A.J.
Abstract : Eukaryotic protein glycosylation is mediated by glycosyl- and oligosaccharyl-transferases. Here, we describe how African trypanosomes exhibit both evolutionary conservation and significant divergence compared with other eukaryotes in how they synthesise their glycoproteins. The kinetoplastid parasites have conserved components of the dolichol-cycle and oligosaccharyltransferases (OSTs) of protein N -glycosylation, and of glycosylphosphatidylinositol (GPI) anchor biosynthesis and transfer to protein. However, some components are missing, and they process and decorate their N -glycans and GPI anchors in unique ways. To do so, they appear to have evolved a distinct and functionally flexible glycosyltransferases (GT) family, the GT67 family, from an ancestral eukaryotic β3GT gene. The expansion and/or loss of GT67 genes appears to be dependent on parasite biology. Some appear to correlate with the obligate passage of parasites through an insect vector, suggesting they were acquired through GT67 gene expansion to assist insect vector (tsetse fly) colonisation. Others appear to have been lost in species that subsequently adopted contaminative transmission. We also highlight the recent discovery of a novel and essential GT11 family of kinetoplastid parasite fucosyltransferases that are uniquely localised to the mitochondria of Trypanosoma brucei and Leishmania major . The origins of these kinetoplastid FUT1 genes, and additional putative mitochondrial GT genes, are discussed.